Letter - McPherson, A. Ian
1949-09-12 038-0005-001 J.C. ? CSCA TELEPHONE: SLOANE 7249-9 TELEGRAMS: CLERIKOFF WESPHONE LONDON CIVIL SERVICE CLERICAL ASSOCIATION 2, UPPER BELGRAVE STREET, LONDON, S.W.1. Our Ref AIM/AH. Your ref General Secretary L.C. White 12th September, 1949. Dear Mr. Tewson, We have recently received a circular letter signed by Mr. R. West, a member of the National Joint Committee for Spanish Relief and Basque Children's Trust Ltd., proposing that the work for the Republican Spaniards should continue and inviting the co-operation of this Association. In the opening paragraph of that circular letter it is stated that a tentative suggestion was made some time ago by Lady Layton to you that possibly the Trade Unions through the T.U.C. might be prepared to carry on the Welfare work on which the National Joint Committee had been engaged in on behalf of Republican Spanish Refugees in this country. My Committee felt that it would be wrong for us to deal with this matter without knowledge as to the attitude of the Trades Union Congress on it. I should be grateful, therefore, if you would be good enough to advise me by or on behalf of the General Council, and whether there is any likelihood that the Trades Union p.t.o. PC attention 14.9.49. DT. 292/946/38/5(I)